The Hypoxia‐Associated High‐Risk Cell Subpopulation Distinctly Enhances the Progression of Glioma - Quan Wan; Xuechao Wu; Jinxu Zhou; Weiqi Wu; Yuanliang Cao; Cuiping Sun; Zheng Li; Zhicheng Gong; Hong Tang; Qilin Li; Junsheng Chu; Qing Wang; et al. (Advanced Science)
Abstract Less‐aggressive lower‐grade gliomas (LGGs) frequently transform into glioblastoma (GBM). Most previous studies of gliomas have not focused on LGG‐original high‐risk subpopulations, which may be one of the most critical hallmarks of glioma progression. In this study, LGG samples are collected to perform single‐cell sequencing (scRNA‐seq) and identify a unique cell subpopulation marked by CDC20, KIF20A and PTTG1, correlating with poor survival in multiple cohorts. Importantly, the CDC20+KIF20A+PTTG1+ cell subpopulation is strongly associated with transforming LGG to GBM according to scRNA‐seq and multiplexed immunofluorescence staining assays. In vitro, ex vivo and in vivo investigations further hint that this cell subpopulation is critical to the proliferation and growth of gliomas, and is associated with the hypoxia core activation. Pharmaceutically and therapeutically, the inhibition of this cell subpopulation showed significant anti‐tumor effects and effective enhancement of the Temozolomide treatment efficiency. These findings provide insights into the therapeutic strategies of glioma progression, highlighting promising ways to avoid early‐stage gliomas developing into advanced gliomas.